Rapid short-pulse (RaSP) sequences improve the distribution of drug delivery to the brain in vivo - Morse,SV; Pouliopoulos,AN; Chan,T; Lin,J; Copping,M; Long,NJ; Choi,JJ (IEEE, 2017)
Focused ultrasound and microbubbles have been shown to locally and noninvasively open the blood-brain barrier. Despite encouraging results in human patients, several performance and safety features, such as poor drug distribution, high drug accumulation along vessels and small sites of red blood cell extravasation, have been unavoidable. We have recently developed a new ultrasound sequence - rapid short-pulse (RaSP) sequence - designed to suppress these adverse features by promoting safer modes of cavitation activity throughout capillaries. In our RaSP sequences, low-pressure short ultrasonic pulses are emitted at kHz pulse repetition frequencies (PRF) and grouped into bursts. We have shown in vitro that RaSP sequences prolong microbubble lifetime and increase their mobility, enhancing the distribution of acoustic cavitation activity. Here we evaluate the ability of RaSP sequences to improve the in vivo performance and safety of ultrasound-mediated drug delivery to the brain.